PENERAPAN PENDEKATAN STUDENT CENTERED LEARNING (SCL) PADA PEMBELAJARAN PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI DI SEKOLAH DASAR NEGERI 22 DAUH PURI DENPASAR - Ni Putu Nita Pratiwi (Jurnal Pendidikan Agama, 2023)
ABSTRACT Along with the development of the era followed by the development of increasingly sophisticated technology, the learning process should use a better approach. Students must be more active in performing and speaking and leave the character as a passive audience. Therefore, the Student Centered Learning (SCL) educational approach was finally raised as a reform step in overcoming the passivity of students, especially in the process of learning Hinduism and ethics. In this case, Hinduism and Ethics Teachers play an important role as mediators in facilitating the implementation of the Student Centered Learning (SCL) method to students, by creating creative innovations in generating active responses from the students themselves. Three problems were raised in this study: the implementation of the Student Centered Learning (SCL) approach, the constraints and efforts to apply the Student Centered Learning (SCL) approach, and the implications of applying the Student Centered Learning (SCL) approach to Hindu religious and ethical education. The theories used to dissect the problems in this study are: (1) Constructivism Theory (Jean Piaget), and (2) Cognitive Theory (Jean Piaget). This type of research is a qualitative research with a psychological approach. The data obtained, collected by interview techniques, literature study and documentation. The data that has been collected is then analyzed using a qualitative descriptive technique. The results of this study indicate that the implementation of the Student Centered Learning (SCL) approach to learning Hinduism and ethics at 22 Dauh Puri Denpasar Elementary School is carried out in 9 (nine) methods including; Small Group Discussion (SGD), Role-Play and Simulation, Discovery Learning, Self-Directed Learning, Cooperative Learning, Contextual Learning (CL), Problem Based Learning (PBL), Collaborative Learning (CbL), and Project Based Learning (PjBL). Regarding the obstacles and efforts to implement the Student Centered Learning (SCL) approach, there are 3 crucial aspects, including; on Teacher Capabilities, Student Capabilities, and the quality of academic facilities and infrastructure. Meanwhile, the implications of applying the Student Centered Learning (SCL) approach to Hinduism and ethics education are seen in 3 (three) fundamental aspects, namely Cognitive Implications, Affective Implications and Psychomotor Implications. Keywords: Student Centered Learning (SCL), Hindu Religious and Moral Education, Elementary School